Proceedings of the 5th International Conference on Applications in Nonlinear Dynamics - In, Visarath; Longhini, Patrick; Palacios, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents collaborative research presented by experts in the field of nonlinear science provides the reader with contemporary, cutting-edge, research works that bridge the gap between theory and device realizations of nonlinear phenomena. The conference provides a unique forum for applications of nonlinear systems while solving practical problems in science and engineering. Topics include: chaos gates, social networks, communication, sensors, lasers, molecular motors, biomedical anomalies, and stochastic resonance. This book provides a comprehensive report of the various research projects presented at the International Conference on Applications in Nonlinear Dynamics (ICAND 2018) held in Maui, Hawaii, 2018. It can be a valuable tool for scientists and engineering interested in connecting ideas and methods in nonlinear dynamics with actual design, fabrication and implementation of engineering applications or devices.
The Cost of Remembering -- Modulation of NF Kinetics and Axonal Morphology Near the Excavation of the Mouse Optic Nerve -- Coupled Crystal Oscillator System and Timing Device -- Nonlinear Computing and Nonlinear Artiﬁcial Intelligence -- The Effects of Ampliﬁcation of ﬂuctuation Energy Scale by Quantum Measurement Choice on Quantum Chaotic Systems: Semiclassical Analysis -- Intentional Nonlinearity in Energy Harvesting Systems -- Nonlinear Operation of Inertial Sensors -- Revealing Network Symmetries Using Time-Series Data -- Analysis of Synchronization of Mechanical Metronomes -- Congestion Avoidance on Networks Using Independent Memory Information -- Analysis of Dynamics of Nonlinear Map Optimization -- Fabrication of YBCO Josephson Junction Using Wet Etching -- Suppression of Stimulated Brillouin Scattering in Optical Fiber Using Boolean Chaos -- Enhanced Anti-Stokes Raman Gain in Nonlinear Waveguides -- Classiﬁcation and Analysis of Chimera States.
Keywords: Dynamics; Nonlinear theories; Nonlinear Optics; Graph theory; System theory; Applied Dynamical Systems; Nonlinear Optics; Graph Theory; Complex Systems